2009
DOI: 10.1021/ie900530d
|View full text |Cite
|
Sign up to set email alerts
|

Pure Hydrogen Production from Pyrolysis Oil Using the Steam−Iron Process: Effects of Temperature and Iron Oxide Conversion in the Reduction

Abstract: In the steam−iron process, relatively pure hydrogen can be produced from pyrolysis oil in a redox cycle with iron oxides. Experiments in a fluidized bed showed that the hydrogen production from pyrolysis oil increases with increasing temperature during reduction. The experimental hydrogen production at nearly 1000 °C with noncatalytic (blast furnace) and catalytic (ammonia synthesis) iron oxide was found to be 1.39 and 1.82 Nm3 of H2/kg of dry oil, respectively. However, this high hydrogen production could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The ion, basically from hematite to magnetite and from Ce 4+ iron oxide and ceria was reduced during the reforming react to Ce 3+ . The reforming products CO, H 2 and C reduce the magnetite to wustite according to following reactions [28]. And then the reoxidizing of wustite to hematite with steam and CO produces H 2 and CO 2 (water-gas shift reaction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion, basically from hematite to magnetite and from Ce 4+ iron oxide and ceria was reduced during the reforming react to Ce 3+ . The reforming products CO, H 2 and C reduce the magnetite to wustite according to following reactions [28]. And then the reoxidizing of wustite to hematite with steam and CO produces H 2 and CO 2 (water-gas shift reaction).…”
Section: Resultsmentioning
confidence: 99%
“…Although iron-based catalysts are known for their high tar cracking activity, Fe 2 O 3 exhibited lower tar conversion capacity compared to CeO 2 at both 600 and 700°C. This is easily understood because of the fact that degradation of tar and iron oxide reductions which are endothermic reactions is more effective at high temperature (≥850°C) [28]. Bleeker et al have studied the gasification of bio-oil in the steam-iron process and reported that the overall conversion of pyrolysis oil to the gas phase increased from 51% at 750°C to 70% at 900°C [30].…”
Section: Effect Of Catalyst On Tar Decompositionmentioning
confidence: 99%
“…Preliminary tests in a bubbling fluidized with a more porous bed material have shown higher carbon to gas conversions as compared to ''inert'' sand. 22 The char itself has combustion and gasification properties comparable to other biomass originated chars. When The formed char can age to form a less reactive char.…”
Section: Implications For Steam Reforming Of Pyrolysis Oilmentioning
confidence: 99%
“…A number of studies have employed non-gaseous fuels including coal [8][9][10][11][12][13], biomass [14][15][16][17] and pyrolysis oil [18,19]. In a syngas chemical looping (SCL) process, the fuel is first converted into syngas in a separate gasification unit.…”
Section: Common Feedstocks For Producing Hydrogenmentioning
confidence: 99%